2019
DOI: 10.1002/ece3.5459
|View full text |Cite
|
Sign up to set email alerts
|

Hypotheses and tracking results about the longest migration: The case of the arctic tern

Abstract: The arctic tern Sterna paradisaea completes the longest known annual return migration on Earth, traveling between breeding sites in the northern arctic and temperate regions and survival/molt areas in the Antarctic pack‐ice zone. Salomonsen (1967, Biologiske Meddelelser, Copenhagen Danske Videnskabernes Selskab, 24, 1) put forward a hypothetical comprehensive interpretation of this global migration pattern, suggesting food distribution, wind patterns, sea ice distribution, and molt habits as key ecological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
(51 reference statements)
4
23
0
Order By: Relevance
“…Light-level geolocators can be fitted to plastic leg rings and seem, in recent studies, to be well tolerated by terns Bevan 2019a, Kürten et al 2019). Use of these devices on arctic terns (Egevang et al 2010, Fijn et al 2013, Alerstam et al 2019 has revealed the extent of their global migration strategies, confirming inferences from observations and ringing recoveries (Salomonsen 1967) of migration routes. However, for technical reasons, such studies have not analysed geolocator data for the periods when birds are in 24-h daylight during the Antarctic summer.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Light-level geolocators can be fitted to plastic leg rings and seem, in recent studies, to be well tolerated by terns Bevan 2019a, Kürten et al 2019). Use of these devices on arctic terns (Egevang et al 2010, Fijn et al 2013, Alerstam et al 2019 has revealed the extent of their global migration strategies, confirming inferences from observations and ringing recoveries (Salomonsen 1967) of migration routes. However, for technical reasons, such studies have not analysed geolocator data for the periods when birds are in 24-h daylight during the Antarctic summer.…”
Section: Introductionsupporting
confidence: 68%
“…The general migration strategies of arctic terns breeding in Europe are well known (Egevang et al , Fijn et al , Alerstam et al ), and birds from Western Europe traverse east for variable distances across the southern Indian Ocean before moving south to the Antarctic (Fijn et al , Alerstam et al ). Daily mean minimum temperatures recorded by the geolocators rapidly decreased as the birds approached the Antarctic and generally remained between 0 and −5°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations